2018
DOI: 10.1364/boe.9.002575
|View full text |Cite
|
Sign up to set email alerts
|

Computational analysis of linear energy modulation for laser thermal coagulation

Abstract: Accurate treatment planning and monitoring are critical factors to ensure safe and effective outcomes of laser thermal coagulation (LTC). Computational and experimental models based upon linear energy modulation were deployed to predict temperature distribution and thermal damage within porcine liver. 1470-nm Gaussian emission was confirmed by using digital imaging and the customized goniometry. The tissue temperature was maintained in the pre-determined range (65~75 °C) to induce thermally destructive volumes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Coagulation is known to occur when the tissue temperature reaches approximately 60 °C because of protein denaturation. However, the extent of the thermal damage is dependent not only on the temperature but also on the tissue’s exposure time at that temperature 17 . The ratio is thus quantified using the temperature- and time-dependent damage parameter , which is calculated using the Arrhenius integral (see Eq.…”
Section: Computational Simulation Of Laser Ablationmentioning
confidence: 99%
See 1 more Smart Citation
“…Coagulation is known to occur when the tissue temperature reaches approximately 60 °C because of protein denaturation. However, the extent of the thermal damage is dependent not only on the temperature but also on the tissue’s exposure time at that temperature 17 . The ratio is thus quantified using the temperature- and time-dependent damage parameter , which is calculated using the Arrhenius integral (see Eq.…”
Section: Computational Simulation Of Laser Ablationmentioning
confidence: 99%
“…These models enable computational simulations to quantify the photothermal effects of laser ablation. Computational simulations of laser ablation consist of calculations of the light transport, the temperature increase, and the degree of thermal damage caused 17 19 . Each step requires an input of numerical information from the previous step, experimental measurement of the tissue properties, and modeling of the tissue structure.…”
Section: Introductionmentioning
confidence: 99%
“…The tissue temperature distribution can be predicted using the bioheat transfer equation (Haemmerich 2022, Hentschel et al 2022. To date, a substantial body of literature has been published on temperature simulations using bioheat transfer equation for LITT (Schwarzmaier et al 1998, Mohammed and Verhey 2005, Paulides et al 2013, Fahrenholtz et al 2015, Shibib et al 2017, Fahrenholtz et al 2018, Truong et al 2018, Bazrafshan et al 2019, Amini and Ahmadikia 2021, Hentschel et al 2022, Hübner et al 2022, Kerbage et al 2022. These studies have focused on various organs, including the liver, prostate, brain, and breasts, among others.…”
Section: Introductionmentioning
confidence: 99%
“…These studies have focused on various organs, including the liver, prostate, brain, and breasts, among others. They can be broadly categorized into three main research purposes: (1) temperature monitoring or preoperative treatment planning (Fahrenholtz et al 2015, 2018, Bazrafshan et al 2019, (2) exploring the relationship between thermal dose, tissue temperature, and ablated volume size (Truong et al 2018, Kerbage et al 2022, and (3) investigating the effects of relevant parameters on temperature simulation and the extent of tissue damage (Shibib et al 2017, Hentschel et al 2022. These investigations provide a reliable theoretical and practical foundation for tissue temperature simulations during LITT.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, an open-loop approach is usually implemented when laser settings are defined before the procedure based on tumor size and location, and these settings remain constant during the whole procedure Some recent works have demonstrated that the use of temperature feedback is beneficial for the laser ablation outcome and for controlling the treated margins [18]. Most of these works regulate the laser power based on the tissue temperature measured with single-point sensors, such as thermocouples and thermistors.…”
Section: Introductionmentioning
confidence: 99%